Genetic examination of historical North Atlantic right whale (Eubalaena glacialis) bone specimens from the eastern North Atlantic: Insights into species history, transoceanic population structure, and genetic diversity. Issue 3 (15th February 2022) - Frasier, Brenna A.; Springate, Leah; Frasier, Timothy R.; Brewington, Seth; Carruthers, Martin; Edvardsson, Ragnar; Harrison, Ramona; Kitchener, Andrew C.; Mainland, Ingrid; Szabo, Vicki E.
Abstract: Species monitoring and conservation is increasingly challenging under current climate change scenarios. For the North Atlantic right whale ( Eubalaena glacialis ) this challenge is heightened by the added effects of complicated and uncertain past species demography. Right whales once had a much wider distribution across the North Atlantic Ocean, although the degree to which right whales in the western and eastern North Atlantic were genetically isolated remains unknown. We analyzed DNA from 24 4th–20th century (CE) right whale bone specimens that were collected from 10 historical and archaeological sites in Iceland, the Faroe Islands, and Scotland. Following mtDNA species identification, we obtained 15‐locus nuclear microsatellite profiles from a subset of eight specimens and compared these to contemporary data from animals remaining in the western North Atlantic population. While some specimens share mtDNA haplotypes with the contemporary population, several new haplotypes were found. Moderate mtDNA and nuclear differentiation between the two regions was identified (mtDNA: F ST = 0.0423, ΦST = 0.041; nuclear DNA: F ST = 0.024). Interpretation of the relationships between animals in the two regions is not simple, and this research highlights the difficulty in conducting such assessments in species with complex histories of unknown structure prior to extensive exploitation.